Detraining Slows and Maintenance Training Over 6 Years Halts Parkinsonian Symptoms-Progression - Hortobágyi, Tibor; Sipos, Dávid; Borbély, Gábor; Áfra, György; Reichardt-Varga, Emese; Sántha, Gergely; Nieboer, Ward; Tamási, Katalin; Tollár, József (Frontiers in Neurology, 2021)
Introduction — There are scant data to demonstrate that long-term non-pharmaceutical interventions can slow the progression of motor and non-motor symptoms and lower drug dose in Parkinson’s disease. Methods ¬— After randomization, the Exercise-only (E, n=19) group completed an initial 3-week-long, 15-session supervised, high-intensity sensorimotor agility exercise program designed to improve postural stability. The Exercise+Maintenance (E+M, n=22) group completed the 3-week program and continued the same program thrice per week for 6ys. The no exercise and no maintenance control (C, n=26) group continued habitual living. In each patient, 11 outcomes were measured before and after the 3-week initial exercise program and then at 3,6,12,18,24,36,48,60, and 72 months. Results — Longitudinal linear mixed effects modeling of each variable was fitted with maximum likelihood estimation and adjusted for baseline and covariates. The exercise program strongly improved the primary outcome, Motor Experiences of Daily Living, by ~7 points and all secondary outcomes (body mass index, disease and not- disease-specific quality of life, depression, mobility, standing balance). In E, detraining effects lasted up to 12 months. E+M further improved the initial exercise-induced gains up to 3 months and the gains were sustained until year 6. In C, symptoms worsened steadily. By year 6, Leva-dopa equivalents increased in all groups but least in E+M. Conclusion: A short-term, high-intensity sensorimotor agility exercise program improved PD symptoms up to a year during detraining but the subsequent 6-y maintenance program was needed to further increase or sustain the initial improvements in symptoms, quality of life, and drug dose.